Association between nonverbal synchrony, alliance, and outcome in psychotherapy: systematic review and meta-analysis - Jennissen, Simone; Huber, Julia; Ditzen, Beate; Dinger, Ulrike (Psychotherapy research, 2025)
Research on nonverbal synchrony (NVS) as a core element in the therapeutic relationship has substantially increased and suggests that NVS influences therapeutic alliance and outcomes. Studies on NVS regarding body movements, vocal pitch, peripheral physiological measures, and hormonal states were included. A random-effects multilevel meta-analysis was performed on 23 publications from 13 trials. There was no significant overall association between NVS and alliance/outcome (r = .03, p = .644). Across modalities, there was a marginally significant association between higher NVS and smaller interpersonal problems (r = .10, p = .084) and a nonsignificant effect for the association between NVS and alliance (r = .06, p = .316), symptomatic outcome (r = -.06, p = .320), and other outcomes (r = .07, p = .255). There was significant heterogeneity between studies (I2 = 56.47). Moderator analyses revealed that vocal pitch synchrony was negatively associated with alliance/outcome (r = -.20, p = .011), while NVS of peripheral physiological parameters was positively correlated with alliance/outcome (r = .32, p = .006). Findings suggest that specific modalities of NVS show specific associations with outcomes. More research is needed to investigate whether NVS across modalities reflects a unified underlying construct.
Veröffentlicht: 25 Nov 2024
Gesehen am 11.07.2025